Research on the Impact of Regional Digitalization on Innovation Performance and Its Boundary Conditions: An Empirical Study Based on Chinese Provincial Panel Data - Yanyan Li; Ziyue Zhu; Shanxing Gao (SAGE Open)
Based on the panel data of 30 provinces from 2016 to 2020, this study empirically analyzes the relationship between regional digitalization level and innovation performance, as well as the moderating effect of three environmental factors: regional science and technology investment, regional educational level, and the development degree of regional intermediary market and legal system. The analysis found that: (1) Different dimensions of digitalization level (digital infrastructure level, digital technology application level, and digital industrialization level) promote innovation performance together. (2) The development of digital-driven innovation is affected heterogeneously by different functional boundary conditions. Regional science and technology investment level, regional education level, and the degree of regional intermediary market and legal system show strengthen effect on the majority relationships between three dimensions of digitalization and innovation performance. Excepting that high regional education level weakens the role of digital industrialization in promoting innovation performance, and the degree of regional intermediary market and legal system show insignificant moderating effect on digital infrastructure level and innovation performance. This research is the first to systematically study the boundary conditions of the relationship between regional digitalization and innovation performance, revealing the necessary conditions for digitalization-driven innovation, deepening the research on the impact of digitalization level on innovation performance, and providing feasible suggestions for policy design and optimization.